2010
DOI: 10.1681/asn.2010010125
|View full text |Cite
|
Sign up to set email alerts
|

Age, Race, Diabetes, Blood Pressure, and Mortality among Hemodialysis Patients

Abstract: Observational studies involving hemodialysis patients suggest a U-shaped relationship between BP and mortality, but the majority of these studies followed large, heterogeneous cohorts. To examine whether age, race, and diabetes status affect the association between systolic BP (SBP; predialysis) and mortality, we studied a cohort of 16,283 incident hemodialysis patients. We constructed a series of multivariate proportional hazards models, adding age and BP to the analyses as cubic polynomial splines to model p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
55
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 53 publications
5
55
1
Order By: Relevance
“…We noted that the African American-Caucasian survival advantage in the setting of significant inflammation was particularly strong among individuals older than 60 years of age, men, and those with diabetes. Consistent with our findings is a recent study of BP among hemodialysis patients by Myers et al 22 that also found the survival advantage for African Americans to be only among their older age group (greater than 40 years) regardless of systolic BP. Furthermore, African American patients with diabetic nephropathy (pre-ESRD) treated in the Department of Veterans Affairs were found to have decreased risk of CVD and mortality when compared with Caucasians.…”
Section: Discussionsupporting
confidence: 93%
“…We noted that the African American-Caucasian survival advantage in the setting of significant inflammation was particularly strong among individuals older than 60 years of age, men, and those with diabetes. Consistent with our findings is a recent study of BP among hemodialysis patients by Myers et al 22 that also found the survival advantage for African Americans to be only among their older age group (greater than 40 years) regardless of systolic BP. Furthermore, African American patients with diabetic nephropathy (pre-ESRD) treated in the Department of Veterans Affairs were found to have decreased risk of CVD and mortality when compared with Caucasians.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, with this estimated rate of underdiagnosis in mind, the risk of diagnoses with dementia and Alzheimer's disease after hemodialysis initiation compared with in the general older adult population is potentially even more substantial than what comparing incidence rates would suggest. Additionally, we identified black and Hispanic patients on hemodialysis as being at an elevated risk of being diagnosed with dementia, which is consistent with findings from the geriatric literature (32); these racial and ethnic differences have been attributed to the greater burden of chronic comorbidity in older adults (33,34) as well as older adults with ESKD (35). It is also possible that these black and Hispanic patients on hemodialysis are now receiving routine medical care, which allows for the diagnosis with dementia after hemodialysis initiation, because dementia is often undiagnosed in this population.…”
Section: Discussionsupporting
confidence: 88%
“…1,2 Recent studies confirmed and extended these findings by illustrating the progressive increase in mortality by degree of albuminuria. 3,4 The excess mortality is due primarily to ESRD 5 and to cardiovascular disease, 6 which share many risk factors. Differential expression of these risk factors within an individual may play an important role in determining which disease ultimately prevails.…”
mentioning
confidence: 99%